HUBUNGAN BERAT BADAN IBU HAMIL PADA TRIMESTER DUA DAN TIGA DENGAN STATUS KESEHATAN JARINGAN PERIODONTAL DI PUSKESMAS ANDALAS PADANG - Rydwan Efendi; Yustini Alioes; Eni Rahmi (Andalas Dental Journal, 2014)
The increasing production of hormone estrogen and progesteron during pregnance known as a risk factors of periodontal disease during pregnance. The other risk factor of periodontal disease during pregnance is obesity, because adipose tissue in obesity person produce pro inflamatory cytokines that influence periodontal status. Both of this risk factors could happen in pregnance woman. During pregnancy, production of hormones estrogen, progesteron and the weight is gained. The aim of this study was to evaluate the relationship between weight during pregnance with periodontal status. This research was an observational analytic with crossectional comparative, with 52 sampels. CPI indeks was used to evaluate the periodontal status meanwhile weight during pregnance was measured by GWS IOM. The resulting data were analyzed by chi-square test. There were significantly differences between pregnance weight at trimester 2nd and 3rd with increasing of the Community Periodontal Indeks.